Climate, urbanization, and conflict: The effects of weather shocks and floods on urban social disorder - David Castells-Quintana; Thomas K. J. McDermott (Asian Development Bank (ADB), 2019)
In this paper, we test the effect of weather shocks and floods on urban social disorder for a panel of large cities in developing countries. We focus on a particular mechanism, namely the displacement of population into (large) cities. We test this hypothesis using a novel dataset on floods−distinguishing those that affected large cities directly from those that occurred outside of our sample of large cities. Floods are found to be associated with faster growth of the population in the city, and in turn with a higher likelihood (and frequency) of urban social disorder events. Our evidence suggests that the effects of floods on urban social disorder occur (mainly) through the displacement of population, and the "push" of people into large cities. Our findings have important implications for evaluating future climate change, as well as for policies regarding adaptation to climate change and disaster resilience.
Keywords: D90; I30; J60; O10; Q00; Q01; Q50; 330; climate change; conflict; floods; migration; rainfall; social disorder; urbanization